Copper‐substituted spinel Zn‐Mg ferrite nanoparticles as potential heating agents for hyperthermia. Issue 8 (6th March 2018) - Ansari, Mohammad; Bigham, Ashkan; Hassanzadeh Tabrizi, Sayed Ali; Abbastabar Ahangar, Hossein
Abstract: Cux Zn0.5‐x Mg0.5 Fe2 O4 ( x  = 0, 0.1, 0.2, 0.3, 0.4, 0.5) ferrite nanoparticles are synthesized via thermal treatment technique using polyvinyl alcohol (PVA) as a capping agent. The effect of Cu 2+ ions substitution on the magnetic and structural properties of ZnMg ferrite nanoparticles is assessed. X‐ray diffraction (XRD) results prove the formation of spinel cubic ferrite with nanocrystalline structure. It is observed by increasing Cu 2+ ions content in Cu 2+ ‐substituted ZnMg ferrite samples, the lattice constant decreases. The field‐emission scanning electron microscopy (FESEM) micrographs indicate that all samples have sizes in nanometer scale with almost spherical morphology and ZnMg ferrite nanoparticles size is increased as the result of Cu 2+ substitution. Magnetic data show that by increasing in Cu 2+ content, the saturation magnetization (Ms) increases up to x  = 0.3 and then declines with the addition of more Cu 2+ ions in the samples. To assess the heat release of Cu 2+ ‐substituted ZnMg ferrite nanoparticles, an alternating magnetic (AC) field is applied. The results show an upward trend for the samples in the temperature vs time chart, as a result of increasing in Ms of the samples. The Cu0.3 Zn0.2 Mg0.5 Fe2 O4 sample exhibits a temperature increase up to 43°C during 510 seconds in the exposure of 125 Oe magnetic field intensity. The cell compatibility of the samples is investigated using osteoblast‐like cells (MG63). Results show that the substitution of Cu 2+ significantly affects the cell compatibility of the ZnMg ferrite nanoparticles.